EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI MTs AL MUKHTARIYAH SUNGAI DUA PORTIBI - Ani Fitri Siregar; Muhammad Syahril Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
Abstract This study aims to know describe the effectiveness of using cooperative learning model of jigsaw type on students’ mathematical problem solving ability on the topic of social arithmetic at the seventh grade students of MTs. Al Mukhtaryah Sungai Dua Portibi. The research was conducted by applying experimental method (one group pretest post test design) with 36 students as the sample and they were taken by using simple random sampling technique from 194 students. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using jigsaw type was 3.27 (very good category) and (b) the average of students’ social arithmetic achievement before using jigsaw type was 64.72 (enough category) and after using jigsaw type was 88.8 (very good category). Furthermore, based on inferential statistic by using pair sample ttest (SPSS 22), the result showed significant value was less than 0.05(0.000<0.05). It means cooperative learning model of jigsaw type was effective used on students’ mathematical problem solving ability on the topic of social arithmetic at the seventh grade students of MTs. Al Mukhtaryah Sungai Dua Portibi. Keywords: cooperative learning model, jigsaw type, students’ mathematical problem solving ability